A conceptual model of suicide in rural areas - O'Connor, Rory (2011)
Context: Suicide is an important public health issue among rural communities although there is no single pattern of suicide in rural areas. Despite this, there are common themes in much of the research evidence on suicide in rural areas. From the published research in the area, a conceptual model of rural suicide has been developed which can be used by clinical and public health services when considering possible routes of intervention.Issue: A conceptual model can be defined as 'a type of diagram which shows a set of relationships between factors that are believed to impact or lead to a target condition'. The model presented here uses the 'Cry of pain/ Entrapment' model of suicide risk to build a framework of factors which are associated with suicide in rural areas. Cross-setting factors associated with suicide rates include gender, poverty, mental illness, substance use, biological factors including apparent genetic risk, coping skills and media coverage of suicide. There are, however, other factors that appear to have particular importance in rural areas. These include rural stressors, such as isolation and political and social exclusion; factors affecting support, including social support, cultural norms on help-seeking, stigma associated with mental illness service availability; factors affecting the decision to self-harm, including modelling and cultural views on self-harm, and issues affecting the likelihood of self-harm resulting in death, including method availability, norms on methods of self-harm and treatment availability after harm occurs. Identifying which of these areas are the greatest local priorities helps to target activity.Lessons learned: This model provides a way of considering suicide in rural areas. Local staff can use it to consider which issues are most relevant to their area. It allows classification of existing interventions, and deciding which other areas of work might be of local value. For researchers and service planners, it provides a way of classifying interventions and describing projects